2021
DOI: 10.1136/bmjopen-2020-046138
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of frailty and pain in hospitalised adult patients in an acute hospital: a protocol for a point prevalence observational study

Abstract: IntroductionFrailty and pain are associated with adverse patient clinical outcomes and healthcare system costs. Frailty and pain can interact, such that symptoms of frailty can make pain assessment difficult and pain can exacerbate the progression of frailty. The prevalence of frailty and pain and their concurrence in hospital settings are not well understood, and patients with cognitive impairment are often excluded from pain prevalence studies due to difficulties assessing their pain. The aim of this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Previous studies reported the association between PS and severity of injury 4 , sex and age 10 , frailty 11 , sleep quality 5 , anxiety 6 , and activities of daily living (ADLs). 12 However, the relationship between those variables and PC has been not demonstrated clearly in hospitalized trauma patients in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the association between PS and severity of injury 4 , sex and age 10 , frailty 11 , sleep quality 5 , anxiety 6 , and activities of daily living (ADLs). 12 However, the relationship between those variables and PC has been not demonstrated clearly in hospitalized trauma patients in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty is a concept used by health care practitioners and is currently understood as a state of increased vulnerability to poor resolution of homeostasis after a stressor event. 4 It is associated with an increased risk of disability, 5 delirium, 6 hospitalization, pain, 7 falls, and death 8 placing individuals at higher risk of adverse outcomes and dependence in daily activities. Therefore, rehabilitation intervention is key in supporting recovery following Background: Aging presents both challenges and opportunities.…”
mentioning
confidence: 99%